Gradual Folding of an Off-Pathway Molten Globule Detected at the Single-Molecule Level. Issue 19 (25th September 2015) - Lindhoud, Simon; Pirchi, Menahem; Westphal, Adrie H.; Haran, Gilad; van Mierlo, Carlo P.M.
Abstract: Molten globules (MGs) are compact, partially folded intermediates that are transiently present during folding of many proteins. These intermediates reside on or off the folding pathway to native protein. Conformational evolution during folding of off-pathway MGs is largely unexplored. Here, we characterize the denaturant-dependent structure of apoflavodoxin's off-pathway MG. Using single-molecule fluorescence resonance energy transfer (smFRET), we follow conversion of unfolded species into MG down to denaturant concentrations that favor formation of native protein. Under strongly denaturing conditions, fluorescence resonance energy transfer histograms show a single peak, arising from unfolded protein. The smFRET efficiency distribution shifts to higher value upon decreasing denaturant concentration because the MG folds. Strikingly, upon approaching native conditions, the fluorescence resonance energy transfer efficiency of the MG rises above that of native protein. Thus, smFRET exposes the misfolded nature of apoflavodoxin's off-pathway MG. We show that conversion of unfolded into MG protein is a gradual, second-order-like process that simultaneously involves separate regions within the polypeptide. Graphical abstract: Highlights: MGs form during folding of many proteins. smFRET tracks folding of an off-pathway MG. smFRET exposes the misfolded nature of apoflavodoxin's off-pathway MG. Conversion of unfolded into molten globular apoflavodoxin is a gradual process.